2015
DOI: 10.1007/s13361-015-1262-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Process of Energy Generation in Pathophysiology by Targeted Metabolomics: Performance of a Simple and Quantitative Method

Abstract: Abstract. Abnormalities in mitochondrial metabolism and regulation of energy balance contribute to human diseases. The consequences of high fat and other nutrient intake, and the resulting acquired mitochondrial dysfunction, are essential to fully understand common disorders, including obesity, cancer, and atherosclerosis. To simultaneously and noninvasively measure and quantify indirect markers of mitochondrial function, we have developed a method based on gas chromatography coupled to quadrupole-time of flig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 43 publications
(41 reference statements)
0
31
0
Order By: Relevance
“…A detailed description of this procedure is given in Cuyàs et al. (2015) and Riera-Borrull et al. (2016) .…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of this procedure is given in Cuyàs et al. (2015) and Riera-Borrull et al. (2016) .…”
Section: Methodsmentioning
confidence: 99%
“…Leucine and valine are essential amino that act as signalling molecules to control energy homeostasis involving lipid metabolism [18,19]. Additionally, leucine can regulate fat metabolism, reduce fat synthesis, promote fat decomposition and increase energy consumption in mammals [20,21].…”
Section: The Correlation Between Metabolomic Results and Hyperlipidemiamentioning
confidence: 99%
“…Several studies have reported the complex metabolism that its phenolic components undergo after ingestion in animal models and, in some cases, in humans. Available data provide information on the metabolites that reach the circulating plasma, but advanced research using targeted metabolomics should be utilized to elucidate the final intracellular metabolites that interact with the molecular targets and their associated biomarkers [183,184].…”
Section: Resultsmentioning
confidence: 99%